A generic framework for augmented concrete mix design: Optimisation of geopolymer concrete considering environmental, financial and mechanical properties. (1st October 2022) - Shobeiri, Vahid; Bennett, Bree; Xie, Tianyu; Visintin, Phillip
Abstract: While concrete mix design has typically focused on the development of low-cost concretes that achieve a particular set of material characteristics, it is now becoming increasingly important to consider environmental impact. This is a challenging problem because concrete mix design, particularly when involving waste materials, is impacted not only by the concrete mix performance but also on material availability and local variation in chemical composition. This variation impacts material performance, financial cost and environmental sustainability. This paper presents a generic framework for mix design optimisation based on a material design and profiling tool coupled with an optimisation algorithm. The framework is then demonstrated for geopolymer concrete (GPC) using a new data-driven mix design tool based on an artificial neutral network to predict mechanical properties (compressive strength and slump) coupled with life-cycle assessment and financial models to quantify mix performance. Together these inputs are used as the basis for single and multi-objective optimisation using a genetic algorithm as part of set of scenarios examining the impact of regional scale transportation scenarios and the chemical composition of binders on the resultant mix properties. The framework's implementation for GPC enabled up to a 50% reduction in CO2-eq emissions compared to equivalent strength experimental mixes, and demonstrated that for a given strength, slump and transportation case the overall CO2-eq emissions can increase by up to 30% where multi-objective optimisation is used (financial and CO2-eq emissions minimization) when compared to minimization of CO2-eq emissions alone. Highlights: A mix optimisation framework is shown considering environmental and financial impact. The framework is demonstrated for geopolymer concrete using demonstration scenarios. Trade-offs are shown between environmental and financial objectives. Results show the importance of material chemical composition and transport distance. Implementation of the framework yields significant reduction in emissions.